5x-60=2x+3

Simple and best practice solution for 5x-60=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-60=2x+3 equation:


Simplifying
5x + -60 = 2x + 3

Reorder the terms:
-60 + 5x = 2x + 3

Reorder the terms:
-60 + 5x = 3 + 2x

Solving
-60 + 5x = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-60 + 5x + -2x = 3 + 2x + -2x

Combine like terms: 5x + -2x = 3x
-60 + 3x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
-60 + 3x = 3 + 0
-60 + 3x = 3

Add '60' to each side of the equation.
-60 + 60 + 3x = 3 + 60

Combine like terms: -60 + 60 = 0
0 + 3x = 3 + 60
3x = 3 + 60

Combine like terms: 3 + 60 = 63
3x = 63

Divide each side by '3'.
x = 21

Simplifying
x = 21

See similar equations:

| w*4w=96 | | (5x+4)=16 | | v1/2=2 | | 6(x-1)-2x=3(x+1)+x | | 19w-10w-5=13 | | (2x+5)=(8x-5) | | 5(n-2)-3(2n+1)=4(1+n) | | 2x^2+5x-41=0 | | 20-14z=-20z-20+16 | | 2x^2+5-41=0 | | 15x/16=1/8 | | 15x/16 | | -18.53+11.6s-9.09=16.1s+6.58 | | -7c-5=-7c^2-3c+8 | | 7x+5y+1=0 | | -2(m-13)+-5=-9 | | 5*8(2*9)/4 | | -(8x+12)=(3x-(-13)) | | 3q-15=9+5q | | (X/7)=-4 | | f(-20)=0.25x+260 | | 12w-10w-2=14 | | Y=(1/2)^2-1/2-42 | | 5*sin(x)=3-cos(2x) | | -16u+11u+10=-20 | | 1.8n=0.5n-11.44 | | 3x+6=-111-10 | | -6.6r=-4.7r+13.3 | | 3.1(f-14)+6.7=12.9 | | 5y+12=92 | | 9x+3=(-9x-10) | | -12.3b-12.95-9.94=-7.71-11.2b |

Equations solver categories